Financial Feasibility Study of Liquid Smoke Industry from Palm Oil Empty Fruit Bunch in Mesuji Regency, Lampung Province - Erdi Suroso; Wisnu Satyajaya; Tanto Pratondo Utomo; Laila Julianti (INSIST, 2017)
Abstract— The objective of this research was to examine the feasibility of liquid smoke production from palm ail empty fruit bunch (EFB). This research was a survey with expert respondents to collect primary data while literatures and reports study as secondary data. The result of study showed that the liquid smoke industry from EFB was feasible to be developed with eligibility criteria Rp. 991,486,765 of NPV ; 2.50 of Net B/C; 36.59 % of IRR ; and 2.83 years of PBP.  The result of sensitivity analysis showed that the liquid smoke industry from EFB more sensitive for liquid smoke price decerasing than raw material and other inputs price increasing.Keywords— Financial Feasibility, Liquid Smoke, EFB.